Analisis Suggestopedia Kenyamanan Ruang Perpustakaan dalam Meningkatkan Daya Konsentrasi Pembaca di Perpustakaan Monumen Pers Nasional Surakarta - Dian Muhammad Rifai; Dina Kristiana Seftianingsih; Indy Rafia; Dea Syahnas Paradita (Jurnal Pustaka Ilmiah, 2024)
This research aims to analyze the implementation of the suggestopedia theory in increasing the concentration of readers at the National Press Monument Library in Surakarta. This research uses a qualitative descriptive study method through the concepts of suggestopology, library science, and interior design. It is intended to find out the extent to which the facilities in the National Press Monument Library in Surakarta can improve the concentration of readers based on the suggestopedia theory. This research uses data collection techniques in the form of observation, and fieldnote interviews to analyze the suggestopedia method in increasing the concentration of readers at the Surakarta Press Monument which is then analyzed using the data triangulation method. The results showed that the facilities in the library, be it spatial layout, room color or music facilities can increase comfort so that it affects the concentration power of the readers and is relevant to the theory of suggestopedia. The conclusion of this research shows that by applying the principles of suggestopedia, the library can be a place that supports and facilitates effective and enjoyable learning. The suggestion from the findings of this research is that other libraries should also apply the principles of suggestopedia to support the comfort of readers so that the number of library visitors can always continue to grow and provide an image that the library is a place worthy of being used as a place to explore knowledge.